2020
DOI: 10.1016/j.ijid.2020.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of bronchoalveolar lavage in the management of patients presenting with lung infiltrates and suspect COVID-19-associated pneumonia: A case report

Abstract: To report a clinical case of a patient with a compatible HRCT scan and two negative SARS-CoV-2 RNA upper respiratory tract specimens but with a confirmed viral infection by BAL (19 days after symptom onset). Methods: Revision of a patient's clinical charts with COVID-19 admitted at INMI L. Spallanzani Hospital Results: Two oropharyngeal swab tests of SARS-CoV-2 by qualitative real-time reverse-transcriptasepolymerase-chain-reaction (RT-PCR) assay were performed at admission (17 days from symptoms onset) and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 7 publications
3
26
0
2
Order By: Relevance
“…In this study, each patient had a swab virus test every other day during their hospitalisation. In this retrospective cohort study, the median negative conversion time of SARS-CoV-2 was 18 days (IQR: [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. This result was similar to that of another study, in which median duration of viral shedding was 17 days (IQR: 12-21) [16].…”
supporting
confidence: 87%
See 1 more Smart Citation
“…In this study, each patient had a swab virus test every other day during their hospitalisation. In this retrospective cohort study, the median negative conversion time of SARS-CoV-2 was 18 days (IQR: [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. This result was similar to that of another study, in which median duration of viral shedding was 17 days (IQR: 12-21) [16].…”
supporting
confidence: 87%
“…Pingzheng Mo et al RNA can be detected in throat swab samples, sputum, alveolar lavage fluid, blood and faeces of patients with COVID-19 [11,12]. Several studies suggested that the virus positive rate of lower respiratory tract specimens, especially bronchoalveolar lavage fluid, was higher than that of upper respiratory specimens in COVID-19 patients [13][14][15]. Bronchoalveolar lavage fluid specimens showed the highest positive rates (93%), followed by sputum (72%), nasal swabs (63%) and pharyngeal swabs (32%) [11].…”
mentioning
confidence: 99%
“…This finding supports the suspicion that patients might become positive at BAL before showing a positive swab. This event has been already described [4] and highlights the effectiveness of BAL in the diagnosis of COVID-19 in particular cases.…”
Section: Discussionsupporting
confidence: 52%
“…Because early studies indicated sputum and BAL samples, if available, can be superior to OPS, especially late in the course of illness [ 23 , 24 , 25 ], and because reports show that viral RNA may become undetectable when the patient is tested later in the course of an illness [ 26 ], our laboratory immediately deployed a risk-based method to assess negative NPS results. LRT specimens, including sputum, tracheal aspirate, and BAL, were sought when the pre-test probability was high and the URT sample yielded a negative result.…”
Section: Lower Respiratory Tract Samplesmentioning
confidence: 99%